Edukasi Aplikasi Mental Responsive Hypnotherapy untuk mengatasi Kecemasan, Hipertensi dan Fobia Pada Usia Subur - Ar-Rohman, Bilqis; Permata, Annissa Devi; Sabit, Achmad Japar Nur; Tasripin, Mellysa Wulandari (Penerbit Widina, Widina Media Utama, 2025)
In today's digital era, the use of mobile devices is increasing and has become an important part of everyday life. To use WebView, developers can insert web pages, web applications, or other internet counters without having to exit the application being used. The purpose of Community Service is to provide education to increase knowledge about the Mental Responsive Hypnotherapy Application to overcome anxiety, hypertension and trauma. increasing knowledge in menopausal women. A pretest was conducted on 45 respondents and a post test on 45 respondents, a total of 90 respondents. Before health education with the Mental Responsive Hypnotherapy Application was carried out, respondents' knowledge about hypertension and healthy lifestyles was in the category of less than 35 people (77.8%), the category was sufficient for 5 people (11.1%) and the category was good for 5 people (11.1%). After being conducted, respondents' knowledge increased with 2 people in the less category (4.4%), 3 people in the sufficient category (6.6%) and 40 people in the good category (89%).ABSTRAKDalam era digital saat ini, penggunaan mobile dervice semakin meningkat dan terlah menjadi bagian penting dari kehidupan sehari-hari. Dengan menggunakan Web View, pengembang dapat menyisipkan halaman web, aplikasi web, atau konten internet lainnya tanpa harus keluar dari aplikasi yang serdang digunakan. Tujuan Pengabdian Kepada Masyarakat memberikan edukasi untuk meningkatkan pengetahuan tentang Aplikasi Mental Responsive Hypnotherapy untuk mengatasi kecemasan, hipertensi dan trauma. peningkatan pengetahuan pada wanita menopause. Dilakukan pretest sebanyak 45 responden dan post test sebanyak 45 responden, jumlah keseluruhan 90 responden. Sebelum pendidikan kesehatan dengan Aplikasi Mental Responsive Hypnotherapy dilakukan, pengetahuan responden tentang hipertensi dan pola hidup sehat ada di kategori kurang 35 orang (77,8%), kategori cukup 5 orang (11,1%) dan kategori baik 5 orang (11,1%). Setelah dilakukan, pengetahuan responden mengalami peningkatan dengan kategori kurang 2 orang (4,4%), kategori cukup 3 orang (6,6%) dan kategori baik 40 orang (89%).